Regulation of Neurological Devices and Neurointerventional Endovascular Approaches for Acute Ischemic Stroke - Loftus, Christopher M.; Hoffmann, Michael; Heetderks, William; Zheng, Xiaolin; Peña, Carlos (Frontiers in Neurology, 2018)
Abstract: The United States Food and Drug Administration (FDA) Center for Devices and Radiological Health (CDRH) is charged with ensuring patients in the United States have timely access to high-quality, safe, and effective medical devices of public health importance. Within CDRH, the Division of Neurological and Physical Medicine Devices (DNPMD) reviews medical technologies that interface with the central and peripheral nervous system (neurotechnologies) including neurointerventional medical devices that are used in the treatment of stroke. Endovascular treatments have demonstrated recent advances in reaching the marketplace and providing more options for patients with acute ischemic stroke and intracranial aneurysms specifically. Depending upon the pathway chosen for regulatory approval, and the evidentiary standard for different regulatory pathways, neurotechnologies can have well-established safety and effectiveness profiles, varying degrees of scientific and clinical uncertainty regarding safety and effectiveness, or when a humanitarian use exists, need only demonstrate a probable benefit and safety to the patient so potentially life-saving treatments can reach the marketplace. Reperfusion therapies have had specific advances in the treatment of stroke patients that originally had limited or no treatment options and for preventative treatments in providing care to patients with intracranial aneurysms to avoid potentially more catastrophic outcomes. Collaboration in multiple forums and environments will be important to continue to foster the neurointerventional technology sector and positively impact clinical medicine, from diagnosing and treating a neurological disorder, to potentially altering the progression of disease, and in many ways, contemporary approved devices have brought a new sense of hope and optimism that serious and otherwise disabling neurological diseases can be treated and in many cases cured with modern therapy. We present here the scope of FDA’s regulatory landscape for neurological devices and neurointerventional endovascular approaches for acute ischemic stroke; this is essential information for those seeking to successfully translate medical device neurotechnologies for patient and consumer use.